Antiproliferative, Anti-inflammatory, and CYP450 Modulation Activities of Deprungsith Formulation and Its Bioactive Components in Psoriasis: Implications for Herb-Drug Interactions - Na-Bangchang, Kesara; Teerachaisakul, Monthaka; Muhamad, Phunuch; Kasemnitichok, Yosita; Sangnarong, Nattida; Boonprasert, Kanyarat; Tarasuk, Mayuri; Plengsuriyakarn, Tullayakorn (Pharmaceutical Research: Recent Advances and Trends Vol. 10, 2024)
Aim: This study investigates the antipsoriasis activities of the Deprungsith formulation and its bioactive components, focusing on their potential inhibitory effects on human cytochrome P450 (CYP450) enzymes. Background: The development of psoriasis is influenced by a combination of genetic, immune, metabolic, environmental, and infectious factors. The hallmark symptoms include red, scaly patches of skin that itch and flake, typically appearing on the scalp, trunk, limbs, and genital area. While psoriasis is rarely life-threatening, its chronic nature can severely impact a patient's quality of life. Experimental Procedure: HaCaT cells and peripheral blood mononuclear cells (PBMCs) from healthy subjects (n=9) and psoriasis patients (n=10) were exposed to Deprungsith formulation, EPMC, ligustilide, and cyclosporin for 24 and 48 hours. The antiproliferative effects were assessed using the MTT assay, while cell apoptosis and cell cycle arrest were analyzed by flow cytometry. The mRNA expression of pro-inflammatory cytokines was determined using RT-PCR. CYP450 inhibitory effects were evaluated using a bioluminescent-based assay. Results: Deprungsith formulation and its bioactive components inhibited HaCaT cell and PBMC proliferation with weak to moderate potency. The combination of EPMC and ligustilide exhibited additive effects. Most test substances arrested cell transition at the sub-G1 and S phases, leading to early and late apoptosis induction. Prolonged exposure (48 hours) reduced necrosis in PBMCs. The mRNA expression of pro-inflammatory cytokines, including IL-6, IL-12p19, IL-23, and TNF-\(α\), was significantly downregulated. Deprungsith formulation, EPMC, ligustilide, and ferulic acid inhibited the activities of CYP1A2, CYP2C9, CYP2D6, and CYP3A4 with weak to moderate potency. Conclusion: Deprungsith formulation and its bioactive components induced cell apoptosis by inhibiting specific cell cycle phases, which was correlated with the downregulation of pro-inflammatory cytokines IL-6, IL-12p19, IL-23, and TNF-\(α\). The risk of adverse drug reactions and toxicity due to potential CYP450 interactions when Deprungsith formulation is considered low. Additional in vivo validation and a more detailed exploration of the clinical relevance would strengthen the findings and provide a clearer therapeutic perspective.